Ernest Hemingway's The old man and the sea - Auer, Jim. (Woodbury, N.Y. : Barron's, 1984)
A guide to reading "The Old Man and the Sea" with a critical and appreciative mind. Includes background on the author's life and times, sample tests, term paper suggestions, and a reading list.
Keywords: Hemingway, Ernest, -- 1899-1961.; Hemingway, Ernest, -- 1899-1961.; American literature -- History and criticism